Treatises on Vocal Hygiene: Channels of Scientific Dissemination in the Nineteenth Century: Music, Science and artistic voice - Comino-Crespo, Francisco José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The correct and healthy use of the artistic voice requires a deep knowledge of the vocal instrument. Medicine and singing find a nexus of union in the scientific discipline of vocal hygiene. The aim of this article, based on a methodology of historical documentation analysis, is to show the relevance of medicine in the development of singing and its diffusion through the publication of treatises on voice hygiene in the 19th century. In addition, the figure of Dr. Faustino Barberá, promoter of scientific dissemination in the context of the official education of singing, is studied.